Cultural Values in the Practices of Communication and Diplomacy - Herudjati Purwoko (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
This paper deals with the importance of cultural values in public diplomacy. The reason is that diplomatic misunderstanding is oftentimes influenced by different cultural values emulated by people who live in different countries. Some cases of cultural discrepancy in communication occurred when Indonesian and Australian people have different viewpoints. Some cases of public diplomacy, selected and discussed in this paper, were interestingly derived from different values.